Residue Network Involved in the Allosteric Regulation of Cystathionine β-Synthase Domain-Containing Pyrophosphatase by Adenine Nucleotides - Viktor A. Anashkin; Anu Salminen; Ekaterina Osipova; Svetlana A. Kurilova; Ilia D. Deltsov; Reijo Lahti; Alexander A. Baykov (ACS, 2022)
Inorganic pyrophosphatase containing regulatory cystathionine β-synthase (CBS) domains (CBS-PPase) is inhibited by adenosine monophosphate (AMP) and adenosine diphosphate and activated by adenosine triphosphate (ATP) and diadenosine polyphosphates; mononucleotide binding to CBS domains and substrate binding to catalytic domains are characterized by positive cooperativity. This behavior implies three pathways for regulatory signal transduction — between regulatory and active sites, between two active sites, and between two regulatory sites. Bioinformatics analysis pinpointed six charged or polar amino acid residues of Desulfitobacterium hafniense CBS-PPase as potentially important for enzyme regulation. Twelve mutant enzyme forms were produced, and their kinetics of pyrophosphate hydrolysis was measured in wide concentration ranges of the substrate and various adenine nucleotides. The parameters derived from this analysis included catalytic activity, Michaelis constants for two active sites, AMP-, ATP-, and diadenosine tetraphosphate-binding constants for two regulatory sites, and the degree of activation/inhibition for each nucleotide. Replacements of arginine 295 and asparagine 312 by alanine converted ATP from an activator to an inhibitor and markedly affected practically all the above parameters, indicating involvement of these residues in all the three regulatory signaling pathways. Replacements of asparagine 312 and arginine 334 abolished or reversed kinetic cooperativity in the absence of nucleotides but conferred it in the presence of diadenosine tetraphosphate, without effects on nucleotide-binding parameters. Modeling and molecular dynamics simulations revealed destabilization of the subunit interface as a result of asparagine 312 and arginine 334 replacements by alanine, explaining abolishment of kinetic cooperativity. These findings identify residues 295, 312, and 334 as crucial for CBS-PPase regulation via CBS domains.